PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA DENGAN MENGGUNAKAN METODE EKSPERIMEN - Mainarti, Riri (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
Theproblems facedarelearning sciencein primary schoolsis still notpresentinreal-world situations.Thisstudyusequalitative and quantitative approaches. Seen from the resultsobtained bythe studentin thelearningof eachcycle, for the first cycle, the results of cognitiveaffectiveaspectsisgood, and for the second cyclesthat 3 aspects is very good. So the conducion is the experiment succd.   Kata kunci : hasil belajar, IPA, metode eksperimen